2020
DOI: 10.3390/jcm9092911
|View full text |Cite
|
Sign up to set email alerts
|

Organ-Sparing Surgery in Testicular Tumor: Is This the Right Approach for Lesions ≤ 20 mm?

Abstract: Background: This study was conducted in order to analyze factors predicting malignancy in patients undergoing organ-sparing surgery (OSS) for small testicular lesions. Methods: Patients with small (£20 mm) marker-negative clinical stage I testicular tumors were managed by OSS with tumor enucleation and frozen section examination (FSE) for the past 15 years at our institution. Benign and malignant cases were compared, focusing on preoperative and postoperative lesion sizes. Results: Eighty-nine patients were en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 28 publications
1
11
0
Order By: Relevance
“…Accordingly, the logistic regression curve revealed all tumours sized ≥ 39 mm to represent malignancy, while tumours ≤ 8 mm involved a 50% chance of being benign. Seven previous studies reporting results from ROC analyses are listed in Table 16 ([ 7 , 23 , 31 , 37 , 41 , 44 , 45 ]). Only one study reported on more than 100 patients [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, the logistic regression curve revealed all tumours sized ≥ 39 mm to represent malignancy, while tumours ≤ 8 mm involved a 50% chance of being benign. Seven previous studies reporting results from ROC analyses are listed in Table 16 ([ 7 , 23 , 31 , 37 , 41 , 44 , 45 ]). Only one study reported on more than 100 patients [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…A total of 3380 abstracts were screened and 283 full‐text articles reviewed. In total, 32 studies were eligible for inclusion [9–16,21,24–46]. There were 22 studies reporting SUS outcomes in 1260 masses in post‐pubertal males, three SUS studies with 212 masses in a mixed population of pre‐ and post‐pubertal males, three studies reporting SUS in 78 masses in pre‐pubertal males, and four studies reporting scrotal MRI outcomes in 142 masses in post‐pubertal males.…”
Section: Evidence Synthesismentioning
confidence: 99%
“…Size of the testicular mass was assessed in 10 studies, which included 334 patients [14,15,24,25,27,28,30,37–39]. We divided them into four size groups: ≤0.5, 0.6–1.0, 1.1–1.5, and >1.5 cm.…”
Section: Evidence Synthesismentioning
confidence: 99%
See 2 more Smart Citations